PENERAPAN METODE NAIVE BAYES DALAM PREDIKSI PENYEBAB KECELAKAAN KERJA CV. DEKA UTAMA - Monica Putri Rahayu; Yusti Farlina (Jurnal Larik: Ladang Artikel Ilmu Komputer, 2021)
Progress of technology and technology is a necessity for its users. The technology has been widely applied in several fields, one example is the presence of technology in the construction sector that makes it easy for its users to make predictions on the factors that cause construction work accidents. An accident at work is an unexpected and unplanned event. Work accidents can hamper the work and will affect the results and the length of time the work itself. One way to minimize workplace accident’s to predict what factors can cause work accidents. Data mining is one way to get information stored in a large number of databases. Work accident data contained in a construction company is only used as a company report. In reality, the data can provide information that is more than just a report. One of the information that can be taken from the company's occupational accident data is information about the prediction of the causes of work accidents. The method for predicting that produces accurate data is the Naive Bayes method. In this research, 78 sample data were processed to produce an accuracy value of 96.15%.